"Triple-Negative Breast Cancer Central Nervous System Metastases From the Laboratory to the Clinic". Issue 1 (January 2021) - Zimmer, Alexandra S.
Abstract : Abstract: Triple-negative breast cancer (TNBC) accounts for 15% to 20% of breast cancers and has an incidence as high as 50% of brain metastases once patients develop advanced disease. The lack of targeted and effective therapies, characteristic of this subtype of breast cancer, is especially evident once central nervous system (CNS) metastases occur. Compared with other subtypes of breast cancer, TNBC patients have the shorter interval from diagnosis to development of brain metastases and the shorter overall survival once they occur, a median of 4 to 6 months. Preclinical studies of TNBC and CNS microenvironment are actively ongoing, clarifying mechanisms and orienting more effective approaches to therapy. While the first drugs have been specifically approved for use in metastatic TNBC, data on their CNS effect are still awaited.